Empowerment Strategy to Eradicate Discrimination Against Women - Abd. Rohman; Sugeng Rusmiwari; Ade Hermawan; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
The issue of violence and discrimination against women is still an international issue, even including the Sustainable Development Goals agenda. Discrimination against women occurs most often is violence, stereotypes and subordination of women. This study used a qualitative method with a descriptive approach. Determination of informants used purposive sampling technique and data analysis using Miles, Huberman, and Saldana models, namely data reduction, data presentation, data condensation, and drawing conclusions/verification. These efforts are made so that women can empower their potential to contribute their interests and talents to create an independent and prosperous life.